The Dual Nature of Trust in Participatory Sciences: An Investigation into Data Quality and Household Privacy Preferences - Danielle Lin Hunter; Valerie Johnson; Caren Cooper (Citizen Science: Theory and Practice)
There is a duality of trust in participatory science (citizen science) projects in which the data produced by volunteers must be trusted by the scientific community and participants must trust the scientists who lead projects. Facilitator organizations are third-party organizations that engage their members in participatory science to enrich their members’ experience at their organization. In Crowd the Tap, we engaged participants through facilitator organizations including high schools, faith communities, universities, and a corporate volunteer program. We used Kruskal Wallis tests and chi-square tests with Bonferroni post hoc tests to assess how data quality and privacy preferences differed across facilitator groups and amongst those who participated in the project independently (unfacilitated). Faith communities provided higher data quality while students provided lower data quality. Data quality in education settings differed based on the level of investment of the project in terms of both time and money as well as student age. We also found that demographic and household characteristics seemed more important in predicting privacy preferences than facilitation. Our results suggest that project leaders can support diverse participation by extending protection of participant privacy and investing in needed resources to support facilitators. They also suggest that education-oriented facilitators may need to prioritize data quality to ensure authentic learning opportunities. Ultimately our results reveal several tradeoffs that project leaders can weigh when deciding to work with facilitators.